ClausTher VR: Claustrophobia Therapy using Virtual Reality - Joe Yuan Mambu; I Gede Purnawinadi; Renaldy Luntungan; Septian Mottoh (SISFOTENIKA, 2021)
Fear or anxiety about a particular situation or object is called phobia, one of the phobias that exists today is Claustrophobia which is a phobia of a closed or small room. The current Claustrophobia therapy method is still traditional, namely by placing the patient in a place that will trigger the patient’s Claustrophobia. This study aims to produce a therapeutic aid and diagnosis of Claustrophobia with Virtual Reality Exposure Therapy method that uses Android-based Virtual Reality and Photogrammetry technology that can be used by medical experts or therapist when conducting therapy to Claustrophobia patients. The research method used is prototyping model. The way to collect data that will be used is by interview and application testing. Researchers used the Unity3D Engine software to create Virtual Reality application and Agisoft Metashape software to create Photogrammetry objects. The application is expected to facilitate the Claustrophobia patients and help people to predict the level of Claustrophobia suffered. The app produced on this research was able to produce the expected virtual environment and had a limited test to user and had similar reaction to a real room. For future research additional rooms and exploration mode may be added, as well as further evaluation to see how this application can be used for therapy tools.